Comparative study of the bioactive compounds of olive products on cardioprotection from ischemia-reperfusion injury in mice with metabolic syndrome. (14th October 2021) - Christodoulou, A; Nikolaou, P E; Tsoumani, M; Efentakis, P; Kostomitsopoulos, N; Dimitriou, C; Ikonomidis, I; Halabalaki, M; Tseti, I; Skaltsounis, A L; Iliodromitis, E; Andreadou, I
Abstract: Background/Introduction: The main bioactive compounds of olive products, oleuropein (OL), hydroxytyrosol (HT), oleocanthal (OC) and oleanolic Acid (OA) exert multiple benefits in cardiovascular diseases. However, their potential cardioprotective effect after chronic administration at a nutritional dose has not been studied in metabolic syndrome (MS). Purpose: We evaluated and compared possible cardioprotective effects of chronic oral treatment with OL, HT, OC and OA in a mouse model of diet-induced MS. Methods: We initially explored if OL, HT, OC, OA exert cardioprotection against ischemia-reperfusion (I/R) injury after chronic administration in healthy animals. The nutritional dose was selected as the equivalent to the estimated daily phenolic intake in humans following the Mediterranean diet. C57Bl6 mice were randomized into 5 groups and treated daily for 6 weeks as followed: i) DMSO 5%, ii) OL (20.6 mg/kg), iii) HT (5.9 mg/kg), iv) OC (11.6 mg/kg), v) OA (17.4 mg/kg). All animals were then subjected to I/R (30/120 min) and infarct size (IS) was determined. In a second cohort, C57Bl6 mice were fed with western diet for 14 weeks to induce MS. At 8th week, mice were randomized into 6 groups: i) Normal Saline (NS), ii) OL, iii) HT, iv) DMSO 5%, v) OC, vi) OA and treated daily with the assigned compound/vehicle for the last 6 weeks. At baseline, 8th and 14th week, body weight, mean arterial blood pressure (MAP) and fasting glucose levels were evaluated. Blood samples were collected at baseline and 14th week for the determination of the lipid profile and the mice were subjected to IR (30/120 min). Results: OL, OC and OA reduced IS in healthy animals (p<0.05 vs. DMSO). Similarly, the IS was significantly reduced in MS mice after OL (19.4±2, 6% vs. NS 34.7±1.6%, p<0.01), OC and OA (12.3±2.9% and 18.3±0.4% vs. DMSO 35.6±4.9%, p<0.0001 and p<0.001). HT failed to reduce the IS in both cohorts. Body weight, glucose, cholesterol and LDL levels were significantly elevated in the control groups, whereas MAP did not change. OL was the only compound that reduced fasting glucose and LDL levels, while OA reduced total cholesterol and LDL levels (p<0.01). OC and HT did not alter the lipidemic parameters. None of the bioactive compounds affected the body weight, MPA and triglyceride levels. Conclusion(s): Chronic treatment with nutritional doses of OL, OC and OA reduce IS in mice with MS; OC displays the most potent cardioprotective effect. OL ameliorates hyperglycemia and decreases LDL, while OA lowers both total cholesterol and LDL. Investigation of the underlying mechanisms and combined treatment with these compounds could emerge novel molecular cardioprotective approaches explaining possible additive beneficial effects in patients with MS. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Operational Program "Competitiveness, Entrepreneurship and Innovation", under the call "RESEARCH – CREATE – INNOVATE" (project code: 5048539).